Analisis Kualitas dan Perkuatan Terowongan Eksplorasi Uranium Eko Remaja Kalan, Kalimantan Barat menggunakan Metode RMR (Rock Mass Rating) - Faizah, Yuni; Cakrabuana, Wira; Kamajati, Dhatu; Rahmawati, Putri (BRIN Publishing, 2020)
Tunnel for Exploration of Uranium Eko Remaja Kalan (TEURK) in West Kalimantan, built-in 1980, is one of the uranium deposit research facilities in Indonesia. The tunnel penetrated Eko Remaja Hill along 618 m, from Remaja to TRK-7 access. Uranium mineralization in this area controlled by dense stockwork veins on metasilt and metasandstone rocks. The high-dense geological structures create some weak zones in the tunnel. These zones are potentially causing rocks and soil slides. Temporary supports made of wood-piles were installed in these zones to support the tunnel. Currently, these piles are not capable at the tunnel, so that rocks and soil slides occurred inside the tunnel. The research aimed to determine the quality of actual rock mass and determine the appropriate type of reinforcement to keep the tunnel safe. Schmidt hammer and scanline surveys on the unsupported zone (50–297 m and 355–538 m depth) carried out to collect the classification parameter data of Rock Mass Rating (RMR). The measurement result shows that the rock mass of TEURK on the depth has an RMR value of 52–71 (fair-good). Reinforcement recommendations for the tunnel are rock bolts and conventional shotcretes installation.